Pengaruh Tingkat Pendidikan, Pendapatan, Kesadaran Dan Pelayanan Terhadap Tingkat Motivasi Masyarakat Dalam Membayar Pajak Bumi Dan Bangunan - Erlindawati Erlindawati; Rika Novianti (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
This research aims to determine partially and simultaneously whether the level of education, level of income, level of awareness, and level of service affect community motivation in paying land and building taxes in the Village of Lemang, West Rangsang District, Meranti Islands Regency. The data analysis technique used is a quantitative analysis using validity and reliability testing, multiple analysis, classic assumption test, t-test, f-test, and coefficient of determination. The results of this research partially indicate that the level of education is positive and significant for community motivation. The level of income is positive and significant for community motivation. The level of awareness is positive and significant for community motivation and the level of service is negative and not significant for community motivation. Simultaneously the level of education, level of income, level of awareness and level of service significantly influence community motivation with a large influence of 71.3%.